First-Principles Study on Optic-Electronic Properties of Charge-Ordered Indium Halide Perovskite Cs2In(I)In(III)Cl6 at High Pressure - Wang, Yajing; Yao, Shunwei; Liu, Xiaolin; Chen, Guohong; Peng, Lin (Frontiers in Nanotechnology, 2021)
Using the first principle method, we studied theoretically in detail the structural, optical, and electronic properties of a charge-ordered indium halide perovskite Cs2In(I)In(III)Cl6 at high pressure. In this structure, In1, In2, and In3 are octahedrally coordinated, whereas In4 is at the center of a pentagonal bipyramid. The charge of In on In1 and In2 sites can be assigned to 3+, while In+ occupies In3 and In4 sites. The results indicated that the band gap decreases, and the electron excitation produces the red-shift of peak value of optical absorption coefficient in visible and infrared regions with increasing pressure, and the reflectivity decreases in visible and infrared regions with increasing pressure. These theoretical results provide a basis for designing related inorganic halide perovskites.